A systematic literature review of burden of disease studies in Europe: next steps and implications for researchers. (20th October 2021) - Devleesschauwer, B; Charalampous, P; Gorasso, V; Plass, D; Monteiro Pires, S; Von der Lippe, E; Haagsma, J
Abstract: Facing the considerable variation in the computation of disability-adjusted life years (DALY), the European Burden of Disease Network (burden-eu) launched a series of systematic literature reviews (SLR) to explore the key variations in the assumptions used in the European burden of disease (BoD) assessments. The studies were evaluated in terms of pre-defined criteria, focusing on data sources used and on specific methodological and normative choices to assess BoD. Preliminary results show a wide variety in methodological assumptions used to quantify DALYs, but also important inconsistencies in the reporting of methods and particular assumptions. For instance, the quantification of uncertainties is not a common practice, even though most authors seem to be aware of the uncertainty in their DALY estimates and discuss uncertainties as an important study limitation. When uncertainties were quantified, different approaches were used, and described using inconsistent nomenclature. The results of the SLR show that there is a clear need for standardized reporting guidelines for DALY estimates. Such a tool could be based on quality assessment checklists already in place for clinical trials and observational studies (PRISMA, STROBE, CRD), and would require inclusion of the DALY's key methodological and normative choices. Standardized DALY reporting guidelines could serve multiple purposes. First and foremost, they would allow to increase the quality of reporting, thereby increasing the transparency and comparability of BoD studies. As a reference document, such guidelines would also help to harmonize nomenclature, which would further increase transparency and comparability. Last but not least, it would also serve as a capacity building tool, supporting researchers in understanding which methods and assumptions underlie the DALY metric. To address this need, the burden-eu network aims to play a driving role in the development of standardized DALY reporting guidelines.